Conservative management of displaced horizontal root fracture - Sanjeev Kunhappan; Sanjay Patil; Pratibha Agrawal (Wolters Kluwer Medknow Publications, 2011)
Traumatic injuries of teeth are the main cause of emergency treatment in dental practice. Radicular fractures in permanent teeth are uncommon, being only 0.5-7% of the cases. Horizontal root fractures are more frequently observed in the maxillary anterior region of young male patients and vary in severity from enamel fractures to avulsions. Fracture occurs often in the middle-third of the root followed by apical and coronal third. The present case report describes a clinical case of a horizontal root fracture located at the middle third of a maxillary left-central incisor treated endodontically after approximating fracture segment with the help of orthodontic appliance. After 6 months follow-up, the tooth was asymptomatic with normal periodontal health.